Social and Political Representation in the Poem Lunatic by Laxmi Prasad Devkota (Rupandehi Campus Journal, 2025)
A literary text can be analysed from multiple perspectives; however, in this article, the poem Lunatic has been examined through inductive reasoning, with a descriptive analysis of its philosophical and socio-political aspects. While making this analysis, the researcher has meticulously referenced figures of speech, imagery, symbols, metaphors, and phrases from the text. The reflective description and findings will enable common readers to understand the poem’s message and the socio-political realities during the Rana Rule. This article will be useful for teachers, learners, and those with a keen interest in exploring the social reality of the time.